2020
DOI: 10.1111/jerd.12673
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of color discrimination tests used in dentistry

Abstract: Objective To evaluate the efficacy of visual discrimination tests used for color research in dentistry. Materials and methods Volunteers (N = 120) were divided in three groups of observers (n = 40; gender‐balanced): S‐dental students; D‐dentists; and L‐laypersons. Two general color discrimination tests (I‐Ishihara and FM‐Farnsworth‐Munsell 100 Hue) and the test of color discrimination competency in dentistry using the VITA Classical shade guide (VC) were performed and data were recorded according to manufactur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Thus, the VSM from two experienced researchers was considered as a reference. A recent study 9 showed that the Farnsworth‐Munsell 100 Hue test or the test for color discrimination competency in dentistry should be applied to evaluate the experience of the observers. Thus, the two experienced researchers performed both tests, exhibiting a superior color discrimination.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, the VSM from two experienced researchers was considered as a reference. A recent study 9 showed that the Farnsworth‐Munsell 100 Hue test or the test for color discrimination competency in dentistry should be applied to evaluate the experience of the observers. Thus, the two experienced researchers performed both tests, exhibiting a superior color discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…The present study was approved by the local Ethics in Research Com- The observers showed normal color vision, which was tested using the 24-plate Ishihara's test for color blindness, 9 and attended a lecture on color matching in dentistry before performing the shade matching procedure. A total of four shade matching sessions were carried out, two for each methodology (VSM and PSA).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations